LARANGAN FASAD FI AL-ARD DALAM TAFSIR AL-QUR’AN DAN REALITAS DEFORESTASI GLOBAL: STUDI KOMPARATIF INDONESIA–BRASIL - Rakhma Haqi; Safwan Mabrur AH (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2025)
The concept of fas?d f? al-ar? constitutes a fundamental principle in the Qur’an that explicitly prohibits all forms of destruction on earth resulting from human actions. In the contemporary context, this concept is highly relevant for interpreting the global environmental crisis, particularly the massive deforestation occurring in tropical forest regions. This article aims to analyze the meaning of fas?d f? al-ar? in classical and contemporary Qur’anic exegesis and to contextualize it within the reality of deforestation in Indonesia and Brazil. Employing a qualitative method based on library research, this study adopts a thematic exegesis (tafs?r maw??‘?) approach and a comparative-contextual analysis. The findings indicate that modern deforestation represents a form of structural fas?d that contradicts Qur’anic principles of balance (m?z?n), the human trust (am?nah) as khal?fah, and the overarching objective of public welfare (ma?la?ah). This article affirms that Qur’anic exegesis possesses both normative relevance and critical capacity in addressing contemporary global environmental issues